Penguatan Program Parenting dalam Meningkatkan Kesadaran Masyarakat tentang Pentingnya Tumbuh Kembang Anak Usia Dini di Dusun Sumber Lingkungan Banjarjo, Kanigoro, Blitar, Jawa Timur - Devi Candra Nindiya; Raras Ayu Prawinda; Dessy Farantika; Devia Purwaningrum (Lifelong Education Journal, 2023)
The age of 0-6 years is a golden period for growth and development cognitive development, language, social emotional, physical motor, religious values ??and morals and art. The growth and development of early childhood occurs very rapidly. Stimulation in children of this age group is very important because it is the foundation for the development of Human Capital because children are healthy and socially optimally grown will grow into productive adults economy. Growth is a change in the size, number, size of the body or members body, which can be measured physically through weighing, measuring height, head circumference measurement, arm circumference measurement and others etc. Growth is limited to structural and physiological changes (physical) (Kemendikbud, 2020). To measure the growth of early childhood parents or PAUD teachers can Measuring weight, height and head circumference is done every month. If you don't gain weight / lose weight / gain weight excessively a period of 2 consecutive months and the child's height does not match his age, immediately consult with PUSKESMAS or pediatrician. Development is an increase in ability or skill in more complex structures and functions of the body in regular patterns and can be predicted as a result of experience and the maturation process. Development is also related to the ability to move, intellectual, social and emotional (Kemendikbud, 2020). Growth and development in early childhood are mutually exclusive related. Many parents assume, children will grow and develop automatically. Even though this assumption is not correct. Early childhood should can grow and develop according to age. If at a certain age, children have not been able to achieve growth and development, then people parents need to be aware of this. To overcome partner problems related to awareness of the importance early childhood development and development, then we are from the community service team provide a solution in the form of Strengthening the Parenting Program in Improving  Public Awareness About the Importance of Child Development. this activity carried out in the form of counseling to mothers who have babies and toddlers as well as posyandu cadres in Dusun Sumber, Lingkungan Banjarjo, Kelurahan Kanigoro, Kecamatan Kanigoro, Kabupaten Blitar. In this parenting program strengthening activity, the method we use are lectures, discussions, and questions and answers. Stages in this service activity includes: 1) Making observations, 2) Coordinating with partners, 3) Carry out strengthening parenting programs in the form of counseling, 4) Follow up Further implementation is carried out by posyandu cadres in coordination with the puskesmas local.